Evaluating Simulations of Interhemispheric Transport: Interhemispheric Exchange Time Versus SF6 Age. Issue 2 (30th January 2019) - Yang, Huang; Waugh, Darryn W.; Orbe, Clara; Patra, Prabir K.; Jöckel, Patrick; Lamarque, Jean‐Francois; Tilmes, Simone; Kinnison, Douglas; Elkins, James W.; Dlugokencky, Edward J.
Abstract: Two recent studies using sulfur hexafluoride (SF6 ) observations to evaluate interhemispheric transport in two different ensembles of atmospheric chemistry models reached different conclusions on model performance. We show here that the different conclusions are due to the use of different metrics and not differences in the performance of the models. For both model ensembles, the multimodel mean interhemispheric exchange time τ ex agrees well with observations, but in nearly all models the SF6 age in the southern hemisphere is older than observed. This occurs because transport from the northern extratropics into the tropics is too slow in most models, and the SF6 age is more sensitive to this bias than τ ex . Thus, simulating τ ex correctly does not necessarily mean that transport from northern midlatitudes into the southern hemisphere is correct. It also suggests that more attention needs to be paid to evaluating transport from northern midlatitudes into the tropics. Plain Language Summary: Transport of air between hemispheres is important as most air pollutants are emitted predominantly in northern midlatitudes, and the rate of this interhemispheric transport influences the global distribution of these gases. Two recent studies analyzed simulations from two different model intercomparison projects and reached different conclusions on the models' ability to simulate the time scale for interhemispheric transport. In this study, we show that the different conclusions are due to the use of different metrics for quantifying the cross‐equator transport time scales, rather than different performances between models. For both groups of models, the mean of the models agrees with observed interhemispheric exchange time τ ex but overestimates the SF6 age at the surface level. This occurs because τ ex is an estimate of the time scale of transport across the equator, whereas the SF6 age in the southern hemisphere quantifies transport from northern midlatitudes into the tropics as well as transport across the equator. Our results indicate that transport into the tropics is generally too slow in models, resulting in too old SF6 ages compared to observed values, with little influence on τ ex . Key Points: Different conclusions from previous studies evaluating model simulations of interhemispheric transport are reconciled The simulated interhemispheric exchange time τ ex agrees well with observations, but the simulated SF6 age in the SH is older than observed Transport from the northern extratropics into the tropics is too slow in most models, which has a larger effect on SF6 age in the SH than τ ex